The Effect of Immunosuppressive Drugs on MDSCs in Transplantation - Fan Yang; Yang Li; Qian Zhang; Liang Tan; Longkai Peng; Yong Zhao (Journal of Immunology Research)
Myeloid-derived suppressor cells (MDSCs) are a group of innate immune cells that regulates both innate and adaptive immune responses. In recent years, MDSCs were shown to play an important negative regulatory role in transplant immunology even upstream of regulatory T cells. In certain cases, MDSCs are closely involved in transplantation immune tolerance induction and maintenance. It is known that some immunosuppressant drugs negatively regulate MDSCs but others have positive effects on MDSCs in different transplant cases. We herein summarized our recent insights into the regulatory roles of MDSCs in transplantation specially focusing on the effects of immunosuppressive drugs on MDSCs and their mechanisms of action. Studies on the effects of immunosuppressive drugs on MDSCs will significantly expand our understanding of immunosuppressive drugs on immune regulatory cells in transplantation and offer new insights into transplant tolerance. We hope to emphasize our concern for the negative effects of immunosuppressive agents on MDSCs, which may potentially attenuate the immune tolerance induction in transplanted recipients.